ANALISIS MODEL TRANSSHIPMENT DALAM PROSES DISTRIBUSI PRODUK SEMEN DI CV BANGUN KREASI ABADI - Joshua Gianfranco; Tasya Mursalina; Muchammad Fauzi (Fakultas Teknik Universitas Tulang Bawang Lampung, 2021)
Bangun Kreasi Abadi is one of the distributors working with PT. Jui Shin Indonesia in marketing and distributing Garuda cement products to several regions in West Java, especially the city of Bandung. In the distribution process, CV Bangun Kreasi Abadi does not send its cement products directly to consumers, but CV. Bangun Kreasi Abadi uses two warehouses as transit points for the delivery of cement products for several regions. The transshipment method has several problems because in the distribution process, products are not sent directly to consumers but must pass through several transit points first. This will result in large costs because the delivery process will be twice as long and will also result in a longer lead time. This study aims to determine the optimal allocation of Garuda cement distribution to produce minimum transportation costs from distributors to warehouses and from warehouses to service points (retailers) using the Transshipment method with the help of Lingo Solver Software. The result of transportation costs from distributors to warehouses is Rp. 25,655,900 and transportation costs from warehouses to retailers of Rp. 26,140,220, the total cost of Garuda cement distribution is Rp. 51,796,120.